Pit and Fissure Sealants (Springer International Publishing, 2018)
This book provides wide-ranging information on current clinical and scientific knowledge on the various aspects of fissure sealing. Trends in the epidemiology of caries are first examined, followed by thorough description of the morphology of pits and fissures and types of sealant. The role of sealants in the prevention of caries is discussed. Diagnostic parameters are presented, along with step-by-step descriptions of clinical procedures for fissure sealing. Chapters are also included on alternative techniques of fissure sealing, sealing of carious fissures, and therapeutic fissure sealing. The final chapter in the book focuses on the cost effectiveness of the procedure. Tooth surfaces with pits and fissures are particularly vulnerable to caries development. Sealants were developed to help manage these sites of the tooth and safeguard the surfaces from decay. This book has been written by acknowledged experts in the field. It will be of value for all dental professionals seeking to deepen their understanding of current knowledge on the science and the clinical application of pit and fissure sealants.